Review on metal contamination in equatorial estuaries in the Brazilian Northeast - Santos, Thays Thayanne Luz; Marins, Rozane Valente; Alves, Letícia Paulino (Frontiers in Earth Science, 2023)
The present study provides an overview and assessment of metals, trace metals, in water, sediment, and biota registered in estuaries of the Equatorial Zone of the Brazilian Northeast (EZBN) to compare the degree of contamination and point out necessary complementary research. The EZBN is characterized by the transition between the humid and hot Amazonian climate and the hot and dry semiarid climate. The spatial distribution identified enrichment for Cu, Pb, Zn, Hg and Fe in the sediment and sequential extraction of metals suggests low to medium mobility of metals along with the environments. Parnaíba River Delta, Curimataú, Anil and Bacanga estuaries were the environments with the lowest sediment quality, identified by Igeo for Pb, Zn, Cu and Fe, related to the enrichment of anthropogenic contributions from domestic sewage and inadequate disposal of wastewater from shrimp farms. However, more studies to determine the natural background levels based on sediment cores and metal speciation are necessary to better differentiate from natural to anthropic sources. Oysters, carnivorous fishes, and crustaceans had the best feedback as a biomonitor for Cu, Pb, Zn and Hg, but the application of biomonitoring needs to be expanded and maintained to observe the potential for environmental degradation that can have significant consequences both for the ecosystem and for human health in the EZBN estuaries.